Aural automaticity as a measure of bilingualism - Feenstra, Henry J.; Wilson, M. Dawn; Fawcett, Nancy K. (Philippine Journal of Linguistics, 1970)
Two groups of French-English bilinguals, 20 predominantly English-speaking and 20 predominantly French-speaking, were placed before a specially-designed apparatus containing 10 coloured keys, five for the left hand and five for the right. In response to two word (e.g. Left red) and full sentence (e.g. Press the red button on the left) instructions, Ss were asked to depress the appropriate key as quickly as possible. The latency of the response, Le, time between the offset of the instruction and the depressing of the appropriate key, was measured and analyzed in two 2 x 2 x 2 analyses of variance. The findings indicated that predominantly English-speaking Ss reacted more quickly to English than to French instructions but did not commit more errors in French than in English. Similarly, predominantly French-speaking subjects showed the same degree of accuracy of response, but reacted faster in French than in English. Differences in reaction time to the two-word and full sentence instruction are considered to be due to differences in the position of the key words (i.e, direction and colour) in English and French sentence structures. The results suggest that latency 'of bilinguals' reaction to aurally-presented stimuli in the two languages may prove to be a useful index of bilingualism.